Creating virtual communities of practice for learning technology in higher education: issues and experiences - Cathy Gunn (Association for Learning Technology, 2004)
Dempster et al .'s paper (2003) describes an example of a community of practice that fits well with the definition given in current literature–one of a few that does not stretch the definition beyond the limits. Some would doubtless argue that communities evolve and cannot be created. This may point to a key element missing from the scenario described, i.e. a compelling reason for users to access the resources and participate in the communities provided for them by learning technologists.